2019
DOI: 10.3390/molecules24050832
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Electron Density Theory Study of the Chemoselectivity, Regioselectivity, and Diastereofacial Selectivity in the Synthesis of an Anticancer Spiroisoxazoline derived from α-Santonin

Abstract: The [3 + 2] cycloaddition (32CA) reaction of an α-santonin derivative, which has an exocyclic C–C double bond, with p-bromophenyl nitrile oxide yielding only one spiroisoxazoline, has been studied within the molecular electron density theory (MEDT) at the MPWB1K/6-311G(d,p) computational level. Analysis of the conceptual density functional theory (CDFT) reactivity indices and the global electron density transfer (GEDT) account for the non-polar character of this zwitterionic-type 32CA reaction, which presents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 41 publications
1
37
0
Order By: Relevance
“…Nitrile oxides are linear propargylic TACs, which have a zwitterionic structure participating in zw-type [64]. An ELF topological analysis of nitrile oxide R3 shows the presence of a V(O) basins integrating a total population of 5.73e indicating the presence of three lone pairs of electrons.…”
Section: Elf Topological Analysis Of the Electronic Structure Of R1 mentioning
confidence: 99%
“…Nitrile oxides are linear propargylic TACs, which have a zwitterionic structure participating in zw-type [64]. An ELF topological analysis of nitrile oxide R3 shows the presence of a V(O) basins integrating a total population of 5.73e indicating the presence of three lone pairs of electrons.…”
Section: Elf Topological Analysis Of the Electronic Structure Of R1 mentioning
confidence: 99%
“…Molecular electron density theory 3 (MEDT) proposed by Domingo in 2016 states that change in electron density is responsible for molecular reactivity in organic reactions. This theory has been widely illustrated for 32CA reactions [4][5][6] as well as for other processes, for which one-step "pericyclic mechanism" has been earlier postulated such as Diels-Alder reactions, 7,8 thermal elimination reaction, 9,10 [3,3] sigmatropic shifts, 11 etc. Initially, topological analysis of the electron localisation function 12 (ELF) and detailed analysis of conceptual density function theory (CDFT) indices 13 at the ground state of the reagents is performed within MEDT.…”
Section: Introductionmentioning
confidence: 99%
“…Monosynaptic basins, denoted by V(A), are associated with non-bonding regions (lone pairs and pseudoradical centers) and disynaptic regions, denoted by V(A,B) are associated with the bonding region between A and B. ELF valence basin populations can be used to recover the Lewis bonding model and provide a reasonably suggestive chemical representation of the molecular system. Topological analysis of the ELF and visualization of ELF localisation domains has been employed in several MEDT studies [4][5][6] to analyse the reactivity of three--atom components [4][5][6] (TACs) participating in 32CAs. This has allowed the classification of TACs into pseudodiradical (pdr-) 15 type, pseudo(mono)radical 16 (pmr-) type, carbenoid (cb-) 15 type and zwitter-ionic (zw-) 5,6,17 type.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[48] Since 2016, MEDT has provided a rationalisation for numerous 32CA reactions. [49][50][51] Herein, an MEDT study of the SP-32CA reactions of PDM 4 and EDA 5 with DIBO 6, experimentally reported by Moran et al, [13] and with acetylene 20, is carried out using quantum chemical procedures at the MPWB1K/6-311G(d,p) computational level in order to understand the origin of the acceleration observed in the SP-32CA reactions of diazoalkanes with strained DIBO 6 (see Scheme 2).…”
Section: Introductionmentioning
confidence: 99%